Drivers of the European Union’s Environmental Performance - Stoian, Mirela; Brad, Laura; Zaharia, Alina (Frontiers in Environmental Science, 2022)
The interactions between nature and humankind produce a series of ecological, social, economic, institutional, technological, and other types of restrictions, which can alter the development of the future society and Earth. Exploring the influencing factors of environmental performance can create better solutions and it can emphasize the gaps from past and current policies. Also, they can contribute to achieve sustainable development. In this regard, more indices are developing for assessing a specific theme that targets sustainability, such as carbon footprint, Environmental Performance Index, or sustainable development index. Thus, this study aims to analyze the influencing factors of Environmental Performance Index (EPI) at an EU level by collecting data between 2010 and 2020, once in 2 years and by using a panel data model. The results were estimated using the Period SUR effect within the generalized least square method and using the White period matrix within the correlation matrix. The results indicate positive relationships between EPI and area under organic farming, circular material use rate, eco-innovation index, energy productivity, ratio of female-to-male labor force participation rate, forest area, Human Development Index, Internet users, livestock production index, new business density, patent applications-residents, tertiary school enrollment, the share of renewable energy consumption in gross final energy consumption, and the proportion of seats held by women in national parliaments. In addition, higher inequality between individuals, natural resources rents, trade volume index, and environmental taxes in total tax revenues seem to constrain the EU’s environmental performance. The results are important both for academicians and policymakers.